Modelling and Motion Analysis of an Automotive Seating Track Using Finite Element Analysis - Sanskar Zode; Shubham Sheshank; Srinivas Challa; Anil C. Mahato; Jay Prakash Tripathi (Applications of Modelling and Simulation, 2024)
This paper aims to improve the design of a seat slider mechanism for an automotive seating system. The seating track mechanism comprises various parts, such as the track bar, upper slider rail, lower slider rail, and locking/unlocking mechanism. The upper rail holds the seat and manikin weight, whereas the lower rail is secured with mounting brackets. A Computer-aided design model of the proposed modified locking/unlocking mechanism of the seating track is created and conducted Finite Element Analysis (FEA). Also, the study includes the motion and dynamic analysis of the seating track mechanism using the bond graph technique by considering the mechanism with an equivalent spring-mass-damper system. The FEA ensured the design strength and its safety regarding failure analysis, whereas the motion analysis confirmed the suitability of the mechanism's kinematics. It is found that the maximum stress is developed at the track bar, i.e., 186.35 MPa, whereas the track displacement reaches its final design position, i.e., 175 mm in 2 s, when the applied force on the track bar is 100 N and on each slider is 20 N. The study ensures an alternative spring-less locking/unlocking mechanism for the seat slider mechanism.